Reverse hall-petch effect in ultra nanocrystalline diamond - Remediakis, Ioannis N.; Kopidakis, Georgios; Kelires, Pantelis C. (My University, 2009)
We present atomistic simulations for the mechanical response of ultra nanocrystalline diamond, a polycrystalline form of diamond with grain diameters of the order of a few nm. We consider fully three-dimensional model structures, having several grains of random sizes and orientations, and employ state-of-the-art Monte Carlo simulations. We calculate structural properties, elastic constants and the hardness for this material; our results compare well with experimental observations. Moreover, we verify that this material becomes softer at small grain sizes, in analogy to the observed reversal of the Hall-Petch effect in various nanocrystalline metals. The effect is attributed to the large concentration of grain boundary atoms at smaller grain sizes. Our analysis yields scaling relations for the elastic constants as a function of the average grain size.
Keywords: Grain boundaries; Nanostructured materials